Workaholics in Urban Society: Diving into the Meaning of Non-Stop Work - Putri, Shinta Hartini; Maulida, Anissa Noor; Sugiarta, Nugraha; Reza, Faisal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Workaholic is a condition of addiction and obsession to keep working. This workaholic phenomenon occurs in one of the companies in the field of photography and videography. This research aims to find out the because of motive and in order to motive. This research uses a qualitative method with Alfred Schutz's approach. Data collection techniques were carried out by interview, observation, book references, and the internet. The technique of determining informants using purposive sampling and data validity techniques using source triangulation. The result of this research is that the motive for employees to become workaholics is experience from the past, the need to continue working, and the organizational environment which is one of the factors while the motive for employees to become workaholics is because they have specific goals to be achieved in the future